2017
DOI: 10.1016/j.ces.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of relative humidity on a nanostructured filter cake – Experimental and modelling approaches

Abstract: In this paper, three different non-hygroscopic nanostructured powders were dispersed in dry air and filtered to create a nanostructured deposit. The relative humidity was then gradually increased from 0 to 85% and the thickness of the deposit continuously measured using a laser trigonometry device. Experimental results showed that for each sample, the pressure drop of the deposit increases when the relative humidity increases, while the bed thickness decreases. The modelling of the pressure drop upon increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…3). These results agree with previous studies investigating the effect of RH on the evolution of the Δp of depth filters loaded with soluble or insoluble particle materials [7][8][9][10][11][12][13][14].…”
Section: Filter Loading Proceduressupporting
confidence: 92%
See 1 more Smart Citation
“…3). These results agree with previous studies investigating the effect of RH on the evolution of the Δp of depth filters loaded with soluble or insoluble particle materials [7][8][9][10][11][12][13][14].…”
Section: Filter Loading Proceduressupporting
confidence: 92%
“…They found that a higher operating RH correlates with an increase in the filter dust holding capacity. Results by Ribeyre et al from experiments with nanosized Al-Zn, C, and SiO 2 on sintered plates at RH up to 85 % support these findings [10].…”
Section: )mentioning
confidence: 72%
“…The thickness and packing density of each filter have been determined by two methods: § A laser trigonometry method (LTM), inspired by the study of Altmann and Ripperger [11], allows obtaining the filter thickness by the measurement of the displacement of a laser between two pictures. For more details, readers may refer to Ribeyre et al [12]. The packing density may be deduced from this thickness and the weighing of a filter with a known surface.…”
Section: Methodsmentioning
confidence: 99%
“…The resistance at 100% RH remained consistent from the initial value throughout the whole intermittent exposure tests. Numerous studies have investigated the interactions of environmental moisture with hygroscopic particles. From a study that examined the growth factor (GF) of aerosol particles in humid conditions, the GF increased with the elevated relative humidity, subsequently to an onset of deliquescence. During INT with 100% RH storage, the particles would dissolve by the environmental moisture, then the particles recrystallize in the supersaturated state when the humidity was lowered.…”
Section: Resultsmentioning
confidence: 99%